1975
DOI: 10.1159/000208158
|View full text |Cite
|
Sign up to set email alerts
|

Some Aspects of Erythropoietic Cell Proliferation in Erythroleukaemia

Abstract: Cytophotometric-autoradiographic investigations on erythropoiesis in erythroleukaemia indicate: (1) the decreased labelling index of erythroblasts is explained by an increased percentage of these cells in G1;(2) ‘megaloblastoid’ basophilic erythroblasts show a more pronounced decrease of their fraction in DNA synthesis than morphological normal cells; (3) ‘megaloblastoid’ early polychromatic normoblasts represent a non-proliferating cell population, and (4) the detected disturbance of cell prolifera… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3

Citation Types

2
1
0

Year Published

1977
1977
1989
1989

Publication Types

Select...
4
1

Relationship

0
5

Authors

Journals

citations
Cited by 6 publications
(3 citation statements)
references
References 4 publications
2
1
0
Order By: Relevance
“…The significant reduc tion of both labelling indices and MGC of erythroblasts in erythroleukaemia (table IV) suggest that mean 3H-TdR incorporation into DNA per DNA-synthesizing ervthroblast (S-phase cell) would be lower in eryth roleukaemia than in normal or vitamin B)2/ folate-deficient megaloblastic bone mar rows. The results are consistent with those of previous investigators who reported a marked decrease in the fraction of DNAsynthesizing cells among basophilic and ear ly polychromatic erythroblasts in erythro-leukaemia bone marrow [11,22,24,26], This defect appeared to be more pron ounced in the erythroblasts with 'megaloblastoid' appearance, a large fraction of which constituted a non-proliferating cell popula tion [22]. Combined cytophotometric and autoradiographic studies further showed that this abnormality was mainly due to an abnormal accumulation of cells in GO or G1 phase, and the presence of 'U' cells, which were unlabelled with • ' !H-TdR had DNA content between diploid (2c) to tetraploid (4c) values [3,22,24,26].…”
Section: Discussionsupporting
confidence: 93%
See 2 more Smart Citations
“…The significant reduc tion of both labelling indices and MGC of erythroblasts in erythroleukaemia (table IV) suggest that mean 3H-TdR incorporation into DNA per DNA-synthesizing ervthroblast (S-phase cell) would be lower in eryth roleukaemia than in normal or vitamin B)2/ folate-deficient megaloblastic bone mar rows. The results are consistent with those of previous investigators who reported a marked decrease in the fraction of DNAsynthesizing cells among basophilic and ear ly polychromatic erythroblasts in erythro-leukaemia bone marrow [11,22,24,26], This defect appeared to be more pron ounced in the erythroblasts with 'megaloblastoid' appearance, a large fraction of which constituted a non-proliferating cell popula tion [22]. Combined cytophotometric and autoradiographic studies further showed that this abnormality was mainly due to an abnormal accumulation of cells in GO or G1 phase, and the presence of 'U' cells, which were unlabelled with • ' !H-TdR had DNA content between diploid (2c) to tetraploid (4c) values [3,22,24,26].…”
Section: Discussionsupporting
confidence: 93%
“…The results are consistent with those of previous investigators who reported a marked decrease in the fraction of DNAsynthesizing cells among basophilic and ear ly polychromatic erythroblasts in erythro-leukaemia bone marrow [11,22,24,26], This defect appeared to be more pron ounced in the erythroblasts with 'megaloblastoid' appearance, a large fraction of which constituted a non-proliferating cell popula tion [22]. Combined cytophotometric and autoradiographic studies further showed that this abnormality was mainly due to an abnormal accumulation of cells in GO or G1 phase, and the presence of 'U' cells, which were unlabelled with • ' !H-TdR had DNA content between diploid (2c) to tetraploid (4c) values [3,22,24,26]. The cytokinetic abnormalities of erythroblasts particularly 'megaloblastoid' cells simulated those re ported in leukaemic myeloblasts [2,20], These and other lines of investigations sug gested that the abnormal growth and prolif eration of erythroblasts in erythroleukaemia probably resulted from neoplastic transfor mation of a stem cell common to both erythroid and granulocytic series [5,12,18,19], It is possible that the impaired DNA metabolism in erythroid precursor cells spe cially 'megaloblastoid' erythroblasts in ery throleukaemia is a characteristic feature, fundamental to the neoplastic or leukaemic nature of these cells.…”
Section: Discussionsupporting
confidence: 93%
See 1 more Smart Citation